2003
DOI: 10.1073/pnas.0235623100
|View full text |Cite
|
Sign up to set email alerts
|

8-Nitroguanosine formation in viral pneumonia and its implication for pathogenesis

Abstract: For many diseases, mediation of pathogenesis by nitric oxide (NO) has been suggested. In this study, we explored NO-induced viral pathogenesis with a focus on nucleic acid damage as evidenced by 8-nitroguanosine formation in vivo. Wild-type mice and littermate mice deficient in inducible NO synthase (iNOS) were infected with influenza or Sendai virus. Formation of 8-nitroguanosine in virusinfected lungs was assessed immunohistochemically with an antibody specific for 8-nitroguanosine. Extensive nitration of RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
149
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(164 citation statements)
references
References 39 publications
7
149
0
Order By: Relevance
“…41,42 NO reacts with superoxide (O 2 2 ) to form peroxynitrite (ONOO 2 ), a highly reactive species that induce nitrative and oxidative DNA damage. In fact, ONOO 2 mediates the formation of 8-oxo-7,8-dihydro-2 0 -deoxyguanosine 43 and 8-nitroguanine, 44,45 which has also been suggested as a potential biomarker of inflammation-related carcinogenesis. 42,46 Recent evidences indicate that 8-nitroguanosine is a highly redox-active molecule 47,48 and that 8-nitroguanine is a mutagenic substance, which preferentially leads to G>T transversions.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…41,42 NO reacts with superoxide (O 2 2 ) to form peroxynitrite (ONOO 2 ), a highly reactive species that induce nitrative and oxidative DNA damage. In fact, ONOO 2 mediates the formation of 8-oxo-7,8-dihydro-2 0 -deoxyguanosine 43 and 8-nitroguanine, 44,45 which has also been suggested as a potential biomarker of inflammation-related carcinogenesis. 42,46 Recent evidences indicate that 8-nitroguanosine is a highly redox-active molecule 47,48 and that 8-nitroguanine is a mutagenic substance, which preferentially leads to G>T transversions.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…This observation indicates that influenza A virus infection is associated with nitrosative stress. Further evidence of involvement of nitrosative stress in influenza A is the demonstration of strong 8-nitroguanosine immunostaining in the cytosol of bronchial and bronchiolar epithelial cells of influenza virus-infected wild-type mice but not iNOS-deficient mice [15]. Moreover, a number of studies have demonstrated that reactive oxygen species contribute to the exacerbation of lung inflammation and lethality in influenza-infected mice, while the use of glutathione precursor promotes survival in influenza-infected mice [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice overexpressing extracellar superoxide dismutase, influenza infection evokes far less lung pathology than in wildtype mice. 7 Induction of the inducible isoform of nitric oxide synthase also contributes notably to lung damage during influenza infection in mice, as such infection was less lethal and produced less lung pathology in mice genetically deficient in iNOS; 31 in wild type mice, administration of the iNOS inhibitor L-NMMA reduced the lethality of influenza. 32 This likely points to a role for peroxynitrite in influenza-associated lung pathology -implying that a reduction in superoxide production could provide protection by decreasing peroxynitrite formation.…”
Section: Nadph Oxidase As a Potential Targetmentioning
confidence: 99%